Comprehensive Family Medicine Approach to Lumbar Radiculopathy in an Obese Patient : A Case Study - Dwi Rahayu, Indriati; Rusnianah, Farida; Fernando, Alexander (Jurnal Ilmu Kedokteran Keluarga, 2025)
Lumbar radiculopathy, often stemming from Herniated Nucleus Pulposus (HNP), presents a significant challenge in primary care, frequently exacerbated by comorbid conditions such as obesity. Family medicine emphasizes a holistic, patient-centered approach, considering both biomedical and psychosocial factors for optimal management. This paper presents the case of a 50-year-old female housewife, diagnosed with Lumbar Radiculopathy due to suspected HNP Lumbal and Grade 1 Obesity. She presented with a one-month history of debilitating left lower back pain (VAS 8/10) radiating to her thigh, calf, and foot, accompanied by numbness. Her symptoms, triggered by exercise and daily activities, significantly impacted her mobility, sleep, and recreational pursuits like aerobics. The diagnostic process employed a holistic framework, integrating anamnesis, physical examination, and family assessments using the Family APGAR and SCREEM tools. Key internal risk factors included her age, obesity, and daily activities involving prolonged standing and stair use. External challenges identified through SCREEM highlighted patient confusion regarding medication adherence during fasting and a tendency for infrequent routine medical check-ups, due to a perceived state of good health. This multifaceted presentation necessitated a tailored management strategy focused on conservative measures, addressing both the radiculopathy and weight management through lifestyle modifications. This case underscores the complexity of managing chronic musculoskeletal pain within a family medicine context, particularly when compounded by obesity. A comprehensive approach, integrating clinical diagnosis with psychosocial and environmental considerations, is crucial for effective patient education, adherence to treatment, and improving functional outcomes.